Digital Fatigue as a Risk Factor for Academic Burnout among Indonesian University Students: A Literature Review - Aditya Andika (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The rapid development of digital learning has significantly transformed higher education in Indonesia, especially after the COVID-19 pandemic accelerated the use of online learning systems. Although digital technology makes learning more flexible and easier to access, spending too much time in front of screens, constant online communication, and heavy academic tasks in online classes have caused digital fatigue among university students. Digital fatigue is a condition of physical, mental, and emotional tiredness caused by intensive use of digital devices and online platforms. This study discusses digital fatigue as a possible cause of academic burnout among Indonesian university students. Using academic papers published between 2021 and 2025, this study reviews the causes, symptoms, and effects of digital fatigue on students’ academic well-being. In conclusion, digital fatigue has become an important psychological and educational problem in Indonesian universities.